(3TQM eNJUQ GHf GdMGLHs - (3GdEjLj, CHh GdaVd, YVO GdOjf, YHO GdQMef Hf CMeO Hf YHO GdZaGQ, J (B756(3g`s ((3jhSa Hf EHQGgje GdCSOjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj HQC GdCfGe hYege HGdEcQGe (B... (3jfMUQ GdeNJUQ aj CehQ CQHYI, GdChd GdeHGOF hgj eG jSehfg ebUhOGH GdPGJ Hd jJhba Ydjg Pdcs
(3BNQgG (B:s
(3BNQgG(B: (3hEPG GYJHQ GdJQLjMGJ aj GdOdGFd hebOeGJgG haj GdMOhO ef LgI eG jbY aj faS GdMOhO aj eaQOGJgG Ke QcHJ HYVgG eY HYV JHGOdGJ aeG ahbgG MUdJ CehQ dG jcGO jfMUQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 295s
(3cTa GdXfhf, L (B2: 1853s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs